2011
DOI: 10.1016/j.tins.2010.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Kainate receptors coming of age: milestones of two decades of research

Abstract: Two decades have passed since the first report of the cloning of a kainate receptor (KAR) subunit. The intervening years have seen a rapid growth in our understanding of the biophysical properties and function of kainate receptors in the brain. This research has led to an appreciation that kainate receptors play quite distinct roles at synapses relative to other members of the glutamate-gated ion channel receptor family, despite structural and functional commonalities. The surprisingly diverse and complex natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
302
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(304 citation statements)
references
References 150 publications
(181 reference statements)
2
302
0
Order By: Relevance
“…KAR EPSCs are also roughly 10% of their grander glutamatergic cousins, and they are also markedly slower, with time constants on the order of 50-100 ms (62,64). This prolonged decay appears to be important for summation, temporal integration, and, ultimately, induction of potentiation (65)(66)(67). Taken together, the studies of KAR EPSCs indicate that the small amplitude of ASIC EPSCs, by itself, is not sufficient to preclude a physiological role.…”
Section: Discussionmentioning
confidence: 96%
“…KAR EPSCs are also roughly 10% of their grander glutamatergic cousins, and they are also markedly slower, with time constants on the order of 50-100 ms (62,64). This prolonged decay appears to be important for summation, temporal integration, and, ultimately, induction of potentiation (65)(66)(67). Taken together, the studies of KAR EPSCs indicate that the small amplitude of ASIC EPSCs, by itself, is not sufficient to preclude a physiological role.…”
Section: Discussionmentioning
confidence: 96%
“…KAR subtypes subserve a variety of functions that depend in part on their subcellular localization (Contractor et al, 2011). It has not yet been possible to link specific KAR subunits with a particular subcellular localization in neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Some iGluRs are also present at presynaptic terminals, where they regulate neurotransmitter release (Pinheiro and Mulle, 2008). Kainate receptors (KARs), composed of various combinations of the five subunits GluK1-5 (formerly referred as GluR5-7, KA1, and KA2), display a variety of functions that concur with the regulation of the activity of synaptic networks by actions at presynaptic and postsynaptic sites (Contractor et al, 2011). The electrophysiological analysis of KAR-subunit deficient mice has indicated that GluK2 and GluK3 are essential components of presynaptic autoreceptors (Contractor et al, 2001;Pinheiro et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Kainic acid (KA), an epileptogenic and neuro-excitotoxic agent, is widely used for inducing neurodegeneration in animal studies (4)(5)(6). It is a specific agonist for kainate receptors, which are ionotropic glutamatergic receptors that modulate transmission and excitability.…”
Section: +mentioning
confidence: 99%